Academic and research approaches in health promotion at Montemorelos University - Jimenez Ortiz, Jose Leonardo (2024)
Objective: This article aims to present the academic and research approaches of Montemorelos University (UM) in health promotion, highlighting the application of innovative methodologies in education and public health interventions. Method: An analysis of the methodologies used in UM’s Master of Public Health program was conducted, including Logical Framework, PRECEDE-PROCEED, Intervention Mapping, and the Transtheoretical Model of Health Behavior Change. The research was based on academic studies and the practical application of these methodologies in institutional and community projects. Results: The applied methodologies enabled students to develop effective interventions for health promotion, significantly improving participants' quality of life. Projects implemented in university, hospital, and community settings demonstrated that evidence-based approaches foster sustainable changes in public health. Conclusion: Montemorelos University has established itself as an innovative institution in health promotion, integrating education, research, and community outreach. The implementation of scientific methodologies strengthens the training of public health professionals, equipping them to face contemporary challenges and promote healthier and more resilient communities.